World War 1 Antiseptic Working Miraculously in Complicated Wounds (Medico Legal Update, 2021)
Introduction: Diabetic foot and complicated ulcers are relatively common occurrence in daily surgical topatient department for managing them various dressing materials and solutions are available. One of suchis acriflavine emulsion.Case Presentation: Both patients were diabetic having large ulcers over leg 2nd was Hepatitis B positivealso having large leg ulcer due to insect bite. In both Acriflavine emulsion was used as dressing material.STSG was performed in both and graft were accepted with uneventful post op courseDiscussion: Acriflavine made from acridine has a local antiseptic property with Antimicrobial and antiviralaction it does have a skin irritant 1 property but to neutralise that glycerine was used in 1:1000 emulsionConclusion: Acriflavine which was used in world war1 as antiseptic solution for war wounds can be usedfor dressing of complicated ulcers and wounds to gainbetter results.